MEDICAL SERVICES OR MEDICAL CARE – AN URGENT ISSUE FOR PUBLIC HEALTH INSTITUTIONS - E. V. Pesennikova; O. V. Gridnev; S. S. Kuchits (Исследования и практика в медицине)
Purpose. To consider the relationship between the concepts of “medical service” and “medical care” in the work of public medical institutions, based on the analysis of normative legal documents of the modern period.Materials and methods. In the course of the research, more than 18 legal and regulatory documents that were published during the period from 1990 to 2017 were analyzed, an analysis of judicial practice and related literature sources (periodicals) was carried out.Results. The analysis made it possible to distinguish the stages in the development of the organizational and legal framework for the provision of paid medical services in the Russian Federation and the dynamics of the relationship between the terms “medical care” and “medical service”. It was revealed that the concept of “medical services” appeared much later and was associated with the development of paid medical services and the need to establish legal aspects of health care. The provision of medical assistance is regulated mainly by public law, and the provision of medical services is governed by private law. The term “medical care” is broader than the “medical service” from the standpoint of the social aspect. At the same time, the concept of “medical service” can be considered more widely than medical care in cases when it is not only about measures aimed at treating the patient, but also about providing additional services to the patient in the process of receiving medical care.Conclusion. Thus, we concluded that the categories of medical care and medical services should not be identified, but also not completely different concepts, but rather enter into a partial intersection relationship. The need to distinguish between the concepts of “medical care” and “medical service” is dictated not only by the category relations or opinion of the population and the medical community, but also by the need for legal support for the process of providing paid medical services with state-owned establishments.